Human And Computer Interaction Through The Utilization Of Online Tourism In Pemalang Regency Indonesia - Tania Putri Novita Sari (FAKULTAS DAKWAH UIN SALATIGA, 2023)
The fact of industrial development where in the city of Pemalang has many good and fascinating tours. So the purpose of this study is to describe human and computer interactions through the use of online tourism in Indonesia, especially specializing in Pemalang city. In this study, the population used is social media users. This research is a research with a qualitative approach with descriptive data type, which is trying to present objective facts in accordance with the conditions that occurred at the time the research was conducted. Data collection techniques in this study using observation, interviews and documentation. The results of this study found that people who are more active on social media. Experiences that can be seen on social media are more interesting so that people are more interested in photos or videos uploaded on social media, such as Instagram, Facebook, Twitter and the Website. With the existence of online tourism, the community introduces more tours that have never been visited before to attract more public interest.